Coccolith species abundances in ODP Site 1082 of the past 750 ka in the region of the Benguela Current (BC) system - Karl-Heinz Baumann (PANGAEA, 2025)
Late Pleistocene coccolith data of ODP Site 1082 from the eastern South Atlantic off Namibia were analysed to document spatial and temporal changes in surface–ocean circulation, upwelling intensity, and associated productivity. The studied site is located on the continental slope close to prominent oceanographic features such as the coastal upwelling mixing area, the open oceanic realm, and the warm-water regime of the Angola Current. Highest numbers of total coccoliths up to >30x10? coccoliths g?^1 sediment were observed during relatively warm periods characterised by decreased upwelling intensity. These elevated numbers of coccoliths are due to higher surface water temperatures and document a domain probably influenced by lower nutrient concentrations in an area where oceanic and filamentous water mix. In contrast, low numbers of coccoliths during glacial periods probably characterise time intervals of enhanced upwelling accompanied by a broad filamentous mixing area. Coccoliths of the genus Gephyrocapsa are the most abundant taxa in samples of Site 1082. Their occurrences are characterised by abrupt changes in the investigated time interval. In addition, Calcidiscus leptoporus, Pseudoemilinia lacunosa, and Reticulofenestra asanoi contribute a common part of the assemblage.